El coro de los maestros carniceros - Erdrich, Louise; Higuera Glynne-Jones, Susana de la; Erdrich, Louise (Madrid : Ediciones Siruela, 2012)
Returning to his quiet German village home after World War I, trained killer Fidelis Waldvogel, accompanied by his wife, leaves to start a new life in America and finds his life irrevocably changed by a new relationship.
Online resource; title from ePub title page (Digitalia, viewed April 1, 2016)
Keywords: Triangles (Interpersonal relations) -- Fiction; World War, 1914-1918 -- Veterans -- Fiction; German Americans -- Fiction; Married people -- Fiction; North Dakota -- Fiction; Immigrants -- Fiction; Butchers -- Fiction; Singers -- Fiction; Domestic fiction; Historical fiction; Romance fiction; Electronic books